2014
DOI: 10.1002/pssa.201431398
|View full text |Cite
|
Sign up to set email alerts
|

Spatially localised luminescence emission properties induced by formation of ring-shaped quasi-potential trap around V-pits in InGaN epi-layers

Abstract: The correlation between surface structural and luminescence properties of InGaN epi-layers grown by metal organic chemical vapour deposition has been investigated. Ringshaped regions with high In-content are observed around V-pits by spatial resolved cathodoluminescence and energy dispersive X-ray spectroscopy. These ring-shaped regions are found to form a potential energy well with depth about 300 meV with respect to the ordinary regions, which can attract carriers and suppress non-radiative recombination. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…An MQW is generally grown on a flat surface, on which macrosteps are not normally desired, 23,24) making the MQW investigated in this work 25) unusual. As an example of QWs with uneven structures, QWs grown on v-pits were reported for InGaNbased LEDs 35,36) and QWs on macrosteps have been reported for AlGaAs on a GaAs bulk substrate. 37,38) The uneven MQW on macrosteps in this study is considered to enhance the compositional modulation, thus increasing the EL output, which is a feature of the MQW in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…An MQW is generally grown on a flat surface, on which macrosteps are not normally desired, 23,24) making the MQW investigated in this work 25) unusual. As an example of QWs with uneven structures, QWs grown on v-pits were reported for InGaNbased LEDs 35,36) and QWs on macrosteps have been reported for AlGaAs on a GaAs bulk substrate. 37,38) The uneven MQW on macrosteps in this study is considered to enhance the compositional modulation, thus increasing the EL output, which is a feature of the MQW in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the spatial extent of In phase separation is still under debate. [32][33][34] However, the dimension of the phase separation is typically on the order of a few to tens of nanometres, much smaller than the sizes of inhomogeneous regions observed in our InGaN epitaxial layers. Accordingly, strictly speaking, the effect of PPM carrier gas shown in our case is to suppress the In-composition fluctuations rather than the phase separation.…”
Section: Resultsmentioning
confidence: 77%
“…It has been reported that InGaN MQWs have an additional lower-energy emission from V-shaped pits, i.e., a facet of the f10 11g plane. 23,24) InGaN in V-shaped pits will cause the shortening of EL wavelengths, indicating that the InGaN has a low In content. There are some reasons why the additional emission originated from the phase-separated component in InGaN.…”
Section: Resultsmentioning
confidence: 99%